2017
DOI: 10.1038/s41598-017-04806-2
|View full text |Cite
|
Sign up to set email alerts
|

Response of Atlantic salmon Salmo salar to temperature and dissolved oxygen extremes established using animal-borne environmental sensors

Abstract: Understanding how aquatic species respond to extremes of DO and temperature is crucial for determining how they will be affected by climate change, which is predicted to increasingly expose them to levels beyond their optima. In this study we used novel animal-borne DO, temperature and depth sensors to determine the effect of extremes of DO and temperature on the vertical habitat use of Atlantic salmon Salmo salar in aquaculture cages. Salmon showed a preference for temperatures around 16.5 to 17.5 °C, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 43 publications
1
87
0
Order By: Relevance
“…However, in lower latitude production areas, such as Ireland and Tasmania, Atlantic salmon can be cultured at temperatures of ca. 15°C and other studies showed a larger range of survival/growth temperatures for Atlantic salmon (Johansson, Ruohonen, Juell, & Oppedal, ; Oppedal, Vågseth, Dempster, Juell, & Johansson, ; Stehfest, Carter, McAllister, Ross, & Semmens, ) up to a maximum of 22°C (Elliott & Elliott, ). Atlantic salmon thermal tolerance seems to be correlated with previous acclimation to temperature, and differences among studies depend on the methods used.…”
Section: Introductionmentioning
confidence: 86%
“…However, in lower latitude production areas, such as Ireland and Tasmania, Atlantic salmon can be cultured at temperatures of ca. 15°C and other studies showed a larger range of survival/growth temperatures for Atlantic salmon (Johansson, Ruohonen, Juell, & Oppedal, ; Oppedal, Vågseth, Dempster, Juell, & Johansson, ; Stehfest, Carter, McAllister, Ross, & Semmens, ) up to a maximum of 22°C (Elliott & Elliott, ). Atlantic salmon thermal tolerance seems to be correlated with previous acclimation to temperature, and differences among studies depend on the methods used.…”
Section: Introductionmentioning
confidence: 86%
“…While some studies have observed avoidance of extremely poor DO conditions (Johansson et al 2007, Stehfest et al 2017, evidence suggests that other environmental factors, such as temperature and light, override behavioural avoidance of moderate DO levels known to reduce feed intake and growth (Johansson et al 2006, Oldham et al 2017, Solstorm et al 2018. Such uneven distribution can result in intense crowding and observed fish densities as much as 20× the stocking density (Oppedal et al 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm the expectation that DO levels are lower in larger cages, but also demonstrate that larger cage sizes can be used without impacting salmon production performance or welfare when ambient DO conditions are sufficient, such as those recorded throughout this study. However, in locations with lower rates of DO replenishment, such as the conditions observed by Stehfest et al (2017) in Macquarie Harbour, Tasmania, shifting to larger cages is not recommended. Even in this study, with low stocking densities and high replenishment rates, limiting DO conditions occurred in the large cages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although evidence of avoidance responses to contamination has been widely reported for many fish species (see review by Araújo et al, 2016), it is recognized that habitat selection processes may be conditioned by several factors other than contamination, such as temperature (Stehfest et al, 2017), pH (Fost and Ferreri, 2015), presence of predators (Scherer and Smee, 2016), and competitors (Dunlop et al, 2006), among others. In the natural environment, organisms are simultaneously exposed to several factors, so it is necessary to understand the extent to which contamination determines the habitat selection process and the ways that these factors affect the avoidance response.…”
Section: Introductionmentioning
confidence: 99%